BADAN PENGELOLA INVESTASI DAYA ANAGATA NUSANTARA: BADAN HUKUM BARU DALAM INVESTASI BUMN DI ERA UU NO. 1 TAHUN 2025 - Agustinus Nugroho Jati; Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the Daya Anagata Nusantara Investment Management Agency (BPI Danantara) as a new legal entity in the management of state-owned enterprises (BUMN) investments in the era of Law No. 1 of 2025. BPI Danantara was established to integrate the management of SOE assets and investments in a professional, transparent, and accountable manner to support sustainable national economic development. This study uses a literature review method by analysing regulations, academic literature, and official documents to explore the concept, position, and impact and challenges of implementing BPI Danantara. The research findings indicate that BPI Danantara plays a strategic role as a national investment management centre that combines the principles of good corporate governance with effective mobilisation of state assets. However, the success of this institution depends on its ability to manage risks, enhance managerial capacity, and ensure independence and transparency in decision-making. This study provides recommendations for strengthening regulations and institutional capacity so that BPI Danantara can contribute maximally to accelerating economic transformation and the management of state-owned enterprise investments.